Resilience, mindfulness, anxiety, and depression within a dual-continua model of mental health approach - Bridget Kennedy; Nicholas Sims-Rhodes; Jacob Avendano; Joseph Mathew; Kyle O'Brien; Carmen Chek; Sarah Sass (Journal of Happiness and Health, 2023)
Mental health research is often focused on alleviating psychological distress rather than increasing well-being. This study approached mental health from a dual-continua model (DCM) framework, which allows for distress and well-being to co-occur. The aims of the present study were to expand upon DCM literature by examining differences in psychological well-being indicators among a broad adult sample with varying levels of depression and/or anxiety symptoms. Our sample was comprised of adults in the United States (n = 1,170) who reported different levels of anxiety, depression, mindfulness, resilience, and satisfaction with life. Participants who reported high anxiety symptoms, high depression symptoms, both anxiety and depression symptoms, or neither were grouped by their level of reported life satisfaction (high or low). We predicted that groups with higher life satisfaction would report higher levels of resilience and trait mindfulness than groups with lower life satisfaction, irrespective of higher levels of anxiety and/or depression, consistent with a DCM of mental health. Our results indicated that higher life satisfaction was associated with higher levels of resilience in all groups except for the high depression with low anxiety group. Higher levels of life satisfaction were also associated with higher trait mindfulness in all but the high anxiety with low depression group. Implications for mental health treatment and prevention are discussed.